Pengabdian Kepada Masyarakat : Inventarisasi Nisan Bersejarah di Desa Jagur Kecamatan Sambas Kabupaten Sambas Kalimantan Barat - Tomi Tomi; Beti Yanuri Posha; Lamazi Lamazi; Deni Irawan; Nursyamsiah Nursyamsiah (Asosiasi Peneliti Dan Pengajar Ilmu Sosial Indonesia, 2024)
This article is a community service report. The purpose of writing this article is to reveal the research of Islamic archaeology in the form of ancient tombstones whose existence has so far caused great concern and has not received attention from the local community or local government. The reporting procedure is based on a qualitative-descriptive approach. Data collection was carried out through interviews, observations and documentation. This research was conducted in Jagur Village, Sambas District, Sambas Regency, West Kalimantan in 2024. The results of the study showed that the identification and detailed analysis of ancient tombstones in Jagur Village showed that the tombstones came from Aceh. Due to the lack of interest from the local community, the ancient tombstones are in a worrying condition, unkempt, damaged, incomplete and many are damaged. It is important for us to work together to preserve and protect the Islamic archaeological heritage found in these tombs, which have provided a rich treasure of knowledge in the past.